Systematic Review: Flipped Classrooms in the Performance of Undergraduate Science Students - Serrano Amarilla, Natalia; Cuetos Revuelta, María José; Manzanal Martínez, Ana Isabel (Journal of Science Education and Technology, 2023)
The sciences are a complex and especially demanding area of study for undergraduate students, particularly in the earlier years, which are a critical period of adaptation to a new educational stage. The use of new teaching models is encouraged to improve their learning, such as flipped classroom (FC), which pursues more meaningful and effective learning that encourages an active role for students. The aim of this study is to perform a systematic review to evaluate the effectiveness of the FC model in learning in the field of experimental and health sciences in higher education during the 2014-2021 period, specifically in students' performance, determining the influence of students' motivation and self-regulation during the process. The phases and quality standards for systematic reviews were complied with in the search for and compilation of the articles analysed. Science students generally view FC as satisfactory. The results show increased motivation and self-regulation and, by extension, a general positive impact on academic performance as benefits. Furthermore, motivation and self-regulation are regarded as key requirements for good performance in an FC environment in the sciences. However, to achieve good results, FC must be applied in such a way that students are able to reflect on their own learning process.
Keywords: flipped classroom; systematic review; academic performance; motivationself-regulation; JCR; Scopus